Nursing ethics through the life span - Bandman, Elsie L.; Bandman, Bertram; Bandman, Elsie L. (Norwalk, Conn. Appleton & Lange, 1990)
This two-part book begins with a discussion of the moral foundations and significance of nurse-client-physician relationships. Models of morality are developed along with values and priorities as guidelines for decision making. These ethics are applied in the second part, beginning with the procreative family and progressing through the life span. Some of the moral-philosophical nursing problems addressed in Part Two include abortion, infancy, the aging, and the dying.
The moral significance of nursing -- Models of the nurse-patient-physician relationship -- Moral implications in codes of nursing -- Traditional models of morality in everyday nursing practice -- Contemporary models of morality in nursing -- Ethical decision making in nursing -- Nursing ethics in the procreative family -- Nursing ethics and the problem of abortion -- Ethical issues in the nursing care of infants -- Ethical issues in the nursing care of children -- Ethical issues in the nursing care of adolescents -- Ethical issues in the nursing care of adults -- Ethical issues in the nursing care of the aged -- Ethical issues in the nursing care of the dying.
Rev. ed. of: Nursing ethics in the life span. c1985.
Includes bibliographies and index.
Keywords: Nursing ethics; Ethics, Nursing